Meningkatkan Prestasi Belajar Fikih Melalui Model Pembelajaran Kooperatif Siswa Kelas V Madrasah Ibtidaiyah Mambaul Huda Desa Panggung Kecamatan Barat Kabupaten Magetan - Sony Widyantoko (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
The government has made various efforts to improve the quality of national education, which, among others, through the improvement of curriculum, procurement of books and learning tools, improvement of infrastructure facilities, improving the quality of school/madrasah management, various training and improving educator qualifications, including in this case is an improvement in the ability of educators in the learning process by using various models and strategies or learning methods, thus enabling learners to always be active in terms of learning. Research methods using action research or action research is a research model that is at the same time practising and theorizing, or combining theory while implementing in practice. The results of the study found that the student's Fiqh learning achievement increased after the Cooperative learning model was applied to class V MI Mambaul Huda West Stage Magetan lesson year 2020/2021. This is evidenced by test results data in cycle III showing an average student score of 92. Similarly, the percentage of completion is 100%.